2005
DOI: 10.1002/gps.1340
|View full text |Cite
|
Sign up to set email alerts
|

Community prevalence of alcohol use and concomitant use of medication—a source of possible risk in the elderly aged 75 and older?

Abstract: Theoretical risks posed by alcohol use are not minimal in the older elderly, though the quantity of alcohol use is not considerable. Physicians and nurses should pay attention to chronic diseases and medications when counselling aged people about alcohol consumption. The question of clinical importance of alcohol-medication interactions needs to be studied further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 31 publications
3
81
1
5
Order By: Relevance
“…But mechanisms underlying the relationships between specifi c life events occurring to older individuals are complex. For example, persons experiencing adverse health events may be advised to reduce alcohol consumption or stop it entirely (see, e.g., Aira et al, 2005). Yet the evidence suggests that moderate alcohol consumption appears to have no effect on glycemic control and a decreased probability of cardiovascular events, the risk of which tends to increase in persons diagnosed with diabetes (Howard et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…But mechanisms underlying the relationships between specifi c life events occurring to older individuals are complex. For example, persons experiencing adverse health events may be advised to reduce alcohol consumption or stop it entirely (see, e.g., Aira et al, 2005). Yet the evidence suggests that moderate alcohol consumption appears to have no effect on glycemic control and a decreased probability of cardiovascular events, the risk of which tends to increase in persons diagnosed with diabetes (Howard et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Older adults frequently use both alcohol and prescription medications. Recent publications show that 86.9% of Finnish adults aged 75 years or over used both alcohol and medications on a regular basis including those known to have an interaction with alcohol [51] , and data from an American prescription medicine assistance program for older persons found that 19% were using alcohol-interactive medications concomitantly with alcohol [52] . Alcohol may interact with medications to reduce cognitive performance.…”
Section: Individual Differences: Comorbidity Genetics and Sex Differmentioning
confidence: 99%
“…This may be due the adverse effects alcohol can have on the health or medication use of those with chronic conditions (Aira et al 2005). Additionally, the risk of multiple chronic diseases increases with age, whereas alcohol misuse and depression are more common among younger age groups.…”
Section: Discussionmentioning
confidence: 99%